Hydrodynamic analysis of the proposed flood bypass channel upstream of Kuching city - Norliza, Aslan Joe (Universiti Malaysia Sarawak, UNIMAS, 2009)
Sarawak River had experienced several disastrous flood events over the past 50 years, with the worst being in 1963, followed by February 2003, January 2004 and January 2009 flood. A flood bypass channel had been suggested as a flood mitigation measure to reduce the flooding effects along the Sarawak River. The proposed flood bypass channel is 8 km long with 250 m base width man-made channel starting from Kampong Paroh to divert a significant portion of flood waters from Sarawak River away from Kuching city to Batang Salak. The main purpose of this project was to review the flooding problems in flood-prone areas of Sarawak River basin and to carry out hydrodynamic analysis on the Sarawak River together with the impacts of the upcoming flood bypass channel. Sarawak River and its floodplains were modeled using one-dimensional hydrodynamic modeling approach, by utilising the Wallingford Software model - InfoWorks River Simulation (RS), coupled with its embedded GIS applications, to obtain the flood hydrographs of the river and its floodplains in extreme flooding condition of January 2004 flood. The simulated results of January 2004 flood obtained showed that the flood bypass channel had been diverting significant portion of flood waters from Sarawak River. Results taken from Batu Kawa showed an average water level reduction of 48.45% which reflects the effectiveness of the flood bypass channel.